Proteomic Responses of the Springtail Folsomia candida to Drought - Yang Wang; Stine Slotsbo; Steffen Y. Bak; Christopher J. Martyniuk; Martin Holmstrup (Insects, 2025)
Springtails are adapted to life in the pore space of soil, where humidity in moist soil is close to saturation. Drought is the most important limiting factor for springtails; however, their molecular and physiological adaptations to low humidity are not well understood. The present study explored the global proteomic drought response of the springtail, Folsomia candida (Isotomidae, Collembola). In relatively dry soil (−360 kPa), adult springtails initially lost body water but re-established the normal body water content over the following two weeks. Nano LC–MS/MS analysis identified a total of 1729 unique proteins. Proteomic analysis and pathway enrichment found that the proteome generally did not show a dramatic induction of proteins in response to drought stress. After an initial down-regulation of pathways related to metabolism and growth, these pathways gradually returned to the same levels as in moist soil. Other pathways such as the cytoskeleton pathway, which is important in cell proliferation and differentiation, were predominantly down-regulated throughout the experiment in drought-exposed animals, which correlated with essentially no somatic growth of the springtails in dry soil. This study facilitates the understanding of the consequences of climate change on soil functioning and fertility.